Designing ELISGAM For Dyslexia Students of SLBN Jombang In EFL Classroom - Imamatul Mujtahidah; Nurul Afidah; Ulfa Wulan Agustina; Noor Faridha (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This research aimed to design the learning media named ELISGAM for dyslexia students that could help them to learn English language. This media application was focused only in listening skill. The research method of this research was Research and Development method (R&D) that adapted ADDIE model that consisted of five procedures, they were : 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. This research involved six dyslexia students of SLBN Jombang in senior high school grade. From those steps, the researcher got the result of the research. 1) The result of media validation was 4,1 (good category), 2) The result of material validation was 4,4 (very good category), 3) The result of dyslexia validation was 4,4 (very good category). Based on the result, the researcher concludes that ELISGAM application was deserved to be used for dyslexia student to learn English language especially in listening skill.